2002
DOI: 10.1074/jbc.m109510200
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Rice RNA- and Microtubule-binding Protein as the Multifunctional Protein, a Peroxisomal Enzyme Involved in the β-Oxidation of Fatty Acids

Abstract: The control of subcellular mRNA localization and translation is often mediated by protein factors that are directly or indirectly associated with the cytoskeleton. We report the identification and characterization of a rice seed protein that possesses both RNA and microtubule binding activities. In vitro UV cross-linking assays indicated that this protein binds to all mRNA sequences tested, although there was evidence for preferential binding to RNAs that contained A-C nucleotide sequence motifs. The protein w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
31
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
3
3
2

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 72 publications
5
31
0
1
Order By: Relevance
“…Two studies demonstrated that the SDS-PAGE profiles of plant proteins that eluted from tubulin and MT affinity chromatography columns were qualitatively similar (5,13), and essentially all proteins that bound to the tubulin affinity columns subsequently co-sedimented with MTs in pelleting assays (14). This indicates that tubulin affinity chromatography can be used to successfully purify MT-binding proteins.…”
mentioning
confidence: 91%
See 2 more Smart Citations
“…Two studies demonstrated that the SDS-PAGE profiles of plant proteins that eluted from tubulin and MT affinity chromatography columns were qualitatively similar (5,13), and essentially all proteins that bound to the tubulin affinity columns subsequently co-sedimented with MTs in pelleting assays (14). This indicates that tubulin affinity chromatography can be used to successfully purify MT-binding proteins.…”
mentioning
confidence: 91%
“…These proteins, often called MT-interacting proteins (MIPs) (2,4), likely bind to MTs as a mechanism to regulate their own activity, to direct their subcellular localization, or as a concentrating mechanism at specific locations within the cell. The interaction of these proteins with MTs is often transient, making it difficult to visualize their interaction with MTs in situ (5). The large surface area provided by the MT network, and the cytoskeleton as a whole, likely serves as a matrix for the binding of hundreds of proteins to an extent that is dependent on cell type and environmental conditions (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Because each half of the YFP is not intrinsically fluorescent, YFP fluorescence is observed only when intermolecular interactions occur between nYFP-and cYFPtagged proteins (Citovsky et al, 2006). All cells were also cobombarded with a plasmid encoding a red fluorescent protein linked to the rice multifunctional protein (RFP-MFP), a wellcharacterized peroxisomal matrix enzyme (Chuong et al, 2002(Chuong et al, , 2005. Coexpressed RFP-MFP served as an internal standard for transformation efficiency as well as a convenient peroxisomal marker to assess colocalizations with BiFC signals and potential changes in peroxisome morphology.…”
Section: Subcellular Localizations Of Fis1a Fis1b and Drp3amentioning
confidence: 99%
“…En otras especies vegetales como pepino, también se han caracterizado distintas isoenzimas MFP expresadas diferencialmente en distintos tejidos de la planta y con distintas actividades en cada caso (Behrends et al, 1988;Preisig-Muller et al, 1994; Guhnemann-Schafer y Kindl, 1995a;. Por último, las proteínas MFP presentan varias regiones de unión a microtúbulos que le permiten el transporte a través de los mismos, e implica que estas proteínas se encuentren asociadas a microtúbulos además de su localización peroxisomal (Chuong et al, 2002; Kindl, 1993), mango (Bojorquez y Gómez-Lim, 1995), colza (Olesen y Brandt, 1995), cotiledones de calabaza (Kato et al, 1996), girasol (Oeljeklaus et al, 2002) y en Arabidopsis (Hayashi et al, 1998b;Germain et al, 2001). El genoma de Arabidopsis contiene tres genes que codifican proteínas KAT.…”
Section: Componentes De La β-Oxidaciónunclassified